Dampak Penambangan Emas Tradisional pada Lingkungan dan Pakan Ternak di Pulau Lombok - Astiti, L. G. S; Sugianti, T. (Universitas Sebelas Maret (UNS), 2014)
The aims of this study were to investigate the impact of traditional mines onenvironment and forage in Lombok Island. The study was conducted in 2013 on forage, waterand soil in 26 villages around the mining site in west Lombok and central Lombok Regency.The result shows that mercury contamination was detected from some location beinginvestigated. The percentage of villages that have mercury contamination was detected in72% location and water contamination with cyanide detected in 66.7% location.Furthermore, the level of mercury in the soil has exceeded the allowable threshold as well asthe content of cyanide in water. In forage samples obtained, there was approximately 0.05ppm of mercury found in 7.7 % of locations. The extent of mercury and cyanide contaminationin environment can provide a low exposure to the surrounding communities and livestock itneeds further awareness to anticipate of hazard on human and livestock health.Keywords: Traditional mining, mercury, cyanide, forage and environment impact